Transportation and centering of mtwo and twisted file systems evaluated by cone beam computed tomography - Torres Carrillo, Angelo José Sócrates (2019)
Objective: To determine the amount of transportation and the centering ability by nickel titanium rotary systems Mtwo and Twisted File, in mesial roots of lower molars using Cone Beam computed tomography. Materials and Methods: Sixty mesial canals of mandibular molars with severe angles of curvature were divided into two groups. After the instrumentation with rotary systems Mtwo and Twisted File, the amount of transportation and centering capacity were evaluated using cone beam computed tomography. Two sections from middle and cervical levels of the canal were recorded. Student t-tests and U by Mann Whitney tests were used for statistical analysis. Results: Less transportation and better centering ability occurred with Twisted File rotary instruments. However, there was no statistically significant difference between the systems (p≤0.05). Canals were transported mostly towards the mesial aspect in the cervical third of the roots, and towards the distal aspect in the mesial third. Conclusions: The rotary instruments Mtwo and Twisted File behaved similarly about the canal transportation and centering, allowing the preparation of curved canals with little deviation.